2014
DOI: 10.1177/0284185113503154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aggressiveness of rectal cancer using 3-T MRI: correlation between the apparent diffusion coefficient as a potential imaging biomarker and histologic prognostic factors

Abstract: Significant correlations were found between mean ADC values and differentiation grade. ADC may be useful as an imaging biomarker of tumor aggressiveness, but it cannot serve as an independent biomarker of advanced rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 37 publications
(36 reference statements)
5
48
1
Order By: Relevance
“…Previous studies reported that pelvic MR imaging was useful for the evaluation of tumor aggressiveness, extramural depth of tumor invasion, and extramural vascular invasion (8)(9)(10)(11). ADC value was widely used especially for the evaluation of tumor aggressiveness and correlated with worse prognostic factors, including pathological T stage, plasmatic CA19-9 level, Ki-67 labeling index, and tumor differentiation grade (9,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that pelvic MR imaging was useful for the evaluation of tumor aggressiveness, extramural depth of tumor invasion, and extramural vascular invasion (8)(9)(10)(11). ADC value was widely used especially for the evaluation of tumor aggressiveness and correlated with worse prognostic factors, including pathological T stage, plasmatic CA19-9 level, Ki-67 labeling index, and tumor differentiation grade (9,12).…”
Section: Discussionmentioning
confidence: 99%
“…ADC value was widely used especially for the evaluation of tumor aggressiveness and correlated with worse prognostic factors, including pathological T stage, plasmatic CA19-9 level, Ki-67 labeling index, and tumor differentiation grade (9,12). Clinical significance of ADC value is likely associated with the fact that malignant tumors contain a high degree of cellularity and interstitial components such as inflammatory cell infiltration, fibrosis, interstitial edema, tumor necrosis, and mucin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…focal lesions [6][7][8][9][10]. Furthermore, the quantitative measurement of apparent diffusion coefficient (ADC) values has also been proposed as a useful imaging biomarker in various types of tumors to differentiate benign and malignant lesions as well as to assess tumor grade and aggressiveness that help predict survival rates [7,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The ADC value and thus the mobility of water molecules decrease with increased tissue cellularity such as inflammation or malignancy. The ADC value may also be used to grade tissue differentiation as shown recently in patients with rectal cancer [17] . The ADC significantly decreased with poorer differentiation of the cancer.…”
Section: New Developments In Ibd Mri Diagnostics: Diffusion-weighted Mrimentioning
confidence: 98%